GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 89523 species occurrences available in GBIF matching the query: Country: New Zealand TaxonKey: Pinophyta. The dataset includes 89523 records from 44 constituent datasets: 2 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 469 records from Phanerogamic Botanical Collections (S). 261 records from Naturalis Biodiversity Center (NL) - Botany. 16 records from University of Alberta Vascular Plant Herbarium (ALTA). 1 records from NCSM PaleoBotany Collection. 271 records from Australia's Virtual Herbarium. 1727 records from iNaturalist Research-grade Observations. 13 records from UCBG TAPIR Provider. 5 records from CONN. 8 records from University of Lethbridge Herbarium (LEA). 1 records from University of California Museum of Paleontology. 127 records from NMNH occurrence DwC-A. 16 records from naturgucker. 80187 records from New Zealand National Vegetation Survey Databank. 133 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 72 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 220 records from Tropicos Specimen Data. 18 records from Natural History Museum (London) Collection Specimens. 2 records from Natural History Museum, Vienna - Herbarium W. 2 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 39 records from Australian National Herbarium (CANB). 1 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 9 records from Paleobiology Database. 2 records from UCD BOTANICAL CONSERVATORY. 84 records from NSW herbarium collection. 16 records from Herbarium Berolinense. 9 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 1 records from USU-UTC Specimen Database. 7 records from Harvard University Herbaria. 9 records from EURISCO, The European Genetic Resources Search Catalogue. 18 records from R. L. McGregor Herbarium Vascular Plants Collection. 1 records from Herbarium Senckenbergianum (FR). 38 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 188 records from Bernice P. Bishop Museum. 5 records from Condon Fossil Collection. 174 records from Royal Botanic Garden Edinburgh Herbarium (E). 4 records from Botany (UPS). 175 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 726 records from New Zealand Biodiversity Recording Network. 1 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 1 records from Wilson Botanical Garden - Las Cruces Biological Station. 4462 records from Allan Herbarium (CHR). 1 records from Vascular Plant Herbarium, Oslo (O). 1 records from The Bergius Herbarium.
Keywords: GBIF; biodiversity; species occurrences